Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/dme.13870
|View full text |Cite
|
Sign up to set email alerts
|

Utility of HbA1c assessment in people with diabetes awaiting liver transplantation

Abstract: AimsTo investigate the relationship between HbA1c and glucose in people with co‐existing liver disease and diabetes awaiting transplant, and in those with diabetes but no liver disease.MethodsHbA1c and random plasma glucose data were collected for 125 people with diabetes without liver disease and for 29 people awaiting liver transplant with diabetes and cirrhosis. Cirrhosis was caused by non‐alcoholic fatty liver disease, hepatitis C, alcoholic liver disease, hereditary haemochromatosis, polycystic liver/kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, given the current limited knowledge of inter-individual differences in PEth synthesis and elimination, additional research is needed to better understand this and improve our understanding of the relationship between self-reported alcohol use and PEth concentrations. Additionally, given that liver disease is associated with shortened red cell survival (Bhattacharjee et al, 2018), our findings that self-reported alcohol use was more strongly associated with PEth among the MALD participants may be explained by the fact that PEth reflects alcohol use over shorter period of time among PWH and comorbid liver disease and would thus be less subject to recall bias.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, given the current limited knowledge of inter-individual differences in PEth synthesis and elimination, additional research is needed to better understand this and improve our understanding of the relationship between self-reported alcohol use and PEth concentrations. Additionally, given that liver disease is associated with shortened red cell survival (Bhattacharjee et al, 2018), our findings that self-reported alcohol use was more strongly associated with PEth among the MALD participants may be explained by the fact that PEth reflects alcohol use over shorter period of time among PWH and comorbid liver disease and would thus be less subject to recall bias.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, in both studies HbA1c was found to be not related to increased risk of SLD. Since the well-established association of HbA1c with higher risk of chronic micro-and macro-vascular complications of type 2 diabetes [37], this finding might be explained by the fact that HbA1c does not accurately reflect glycemic control in individuals with diabetes and cirrhosis [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c levels can be affected by many factors in addition to mean plasma glucose (MPG) level, and considerable variation can be seen even among individuals with similar mean blood glucose levels. Therefore, interpreting the HbA1c results requires consideration of many factors, such as age, anaemia/haemoglobinopathies, pregnancy, and renal and hepatic disease . To overcome this limitation, the HGI was introduced as an alternative method of determining interindividual variations in HbA1c by Hempe et al in 2002 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interpreting the HbA1c results requires consideration of many factors, such as age, anaemia/haemoglobinopathies, pregnancy, and renal and hepatic disease. [18][19][20][21][22] To overcome this limitation, the HGI was introduced as an alternative method of determining interindividual variations in HbA1c by Hempe et al in 2002. 2 Several studies have subsequently demonstrated that HGI can reflect the biovariability of HbA1c.…”
Section: Discussionmentioning
confidence: 99%